2007
DOI: 10.1021/ic062133c
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinic Platinum Complexes with 8-Thiotheophylline Derivatives:  Synthesis, Characterization, and Antiproliferative Activity

Abstract: The platinum mixed-phosphine complexes (SP-4,2)-[PtCl(8-MTT)(PPh3)(PTA)] (2) and cis-[Pt(8-MTT)2(PPh3)(PTA)] (3) (MTTH2 = 8-(methylthio)theophylline, PTA = 1,3,5-triaza-7-phosphaadamantane) have been prepared from the precursor cis-[PtCl2(PPh3)(PTA)] (1), which has been fully characterized by X-ray diffraction determination. Antiproliferative activity tests indicated that the presence of one lipophilic PPh3 and one hydrophilic PTA makes 1-3 more active than the analogues bearing two PPh3 or two PTA. The reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 29 publications
(29 reference statements)
0
26
0
Order By: Relevance
“…Two ruthenium-based anticancer drugs, NAMI-A - [ImH][trans-RuCl 4 (DMSO)(Im)] and KP1019 -[H 2 Ind][transRuCl 4 (HInd) 2 ] (HInd = 1H-indazole), have successfully completed phase 1 clinical trials and are scheduled to enter phase 2 trials in the near future [22][23][24]. Phosphine complexes of various transition metals (Au, Ag, Cu, Ru, Rh, Pt, Pd) have been evaluated as potential antitumor agents in various human tumor cell lines [25][26][27][28][29][30]. In the Au complexes, for instance, the observed activity has been attributed to the presence of the phosphine ligands, since similar complexes without them had a very low activity [31].…”
Section: Introductionmentioning
confidence: 99%
“…Two ruthenium-based anticancer drugs, NAMI-A - [ImH][trans-RuCl 4 (DMSO)(Im)] and KP1019 -[H 2 Ind][transRuCl 4 (HInd) 2 ] (HInd = 1H-indazole), have successfully completed phase 1 clinical trials and are scheduled to enter phase 2 trials in the near future [22][23][24]. Phosphine complexes of various transition metals (Au, Ag, Cu, Ru, Rh, Pt, Pd) have been evaluated as potential antitumor agents in various human tumor cell lines [25][26][27][28][29][30]. In the Au complexes, for instance, the observed activity has been attributed to the presence of the phosphine ligands, since similar complexes without them had a very low activity [31].…”
Section: Introductionmentioning
confidence: 99%
“…Tests with the cis platin‐sensitive cells T2 showed that complex 4 displays a significantly better activity than the others. The antiproliferative activities of related PTA Ru, and Pt complexes were correlated with their solubility in lipophilic media, which is connected with the ability of the compound to cross the lipophilic membranes of the cell. If the antiproliferative action mechanism involves the reaction of the compound with internal components of the cell, only those complexes capable of crossing membranes can react with internal cell components.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, the recent data on tumor‐specific cytotoxicity of novel Ru‐arene‐CAP (RACAP) complexes demonstrate that biochemical behavior of CAP compounds may considerably deviate from that of their PTA counterparts. Therefore, though it is established that square‐planar palladium(II) and platinum(II) complexes of PTA possess low cytotoxic activity, we performed in‐vitro experiments aimed at determination of cytotoxicity of novel compounds of CAP reported herein. Both Pd(II) and Pt(II) complexes were found to be sufficiently stable in the diluted aqueous solutions having 100 mM NaCl background under pseudo‐physiological conditions.…”
Section: Resultsmentioning
confidence: 99%